Gender mainstreaming and the benchmarking fallacy of women in political decision-making - Meier, Petra; Lombardo, Emanuela; Bustelo, Maria; Maloutas, Maro Pantelidou (The Greek Review of Social Research, 2016)
In this article the authors analyse the extent to which an explicitly gendered issue such as the position of wo/men in political decision-making has been approached from a gender mainstreaming perspective. They do so by exploring how the issue has been framed in three countries, the Netherlands, Spain, and Greece, and in the European Union. The analysis enables them both to provide a state of the art of how gender in political decision-making has been dealt with throughout the last decade in the selected case-studies and to offer insights on the potential for a gender mainstreaming approach of topics in which sex-related inequality is explicit. The main argument is that such policy issues contain a benchmarking fallacy. The easiness with which they can be quantified opens the door for an analysis and solution of problems of gender inequality in terms of numbers, without tackling underlying structural problems.